The Influence of Service Quality and e-WOM Promotion on Purchase Intention through Brand Image and Brand Trust in Dental Clinics - Imanuel, Eunike; Ruswanti, Endang (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine each variable that influences its respective role. For example, the influence of product quality on e-WOM, brand image, brand trust, and purchase intention at a dental clinic in Jakarta. This study involved 150 dental clinic patients in Jakarta from December 2023 to February 2024. SmartPLS 4.0 software was used to conduct data analysis using the Structural Equation Model (SEM). The study found that Service Quality, Electronic Word of Mouth, Brand Image, and Brand Trust have a positive effect on Purchase Intention, both directly and indirectly. Service Quality (SQ) has a positive effect on perceived Brand Image, and Quality of Brand Trust (BT) has a positive effect on Brand Trust (BT). This also supports this study. e-WOM has a positive impact. Good service quality at a dental clinic can create a positive perception in the minds of consumers regarding the clinic's image. Positive information from other customers on social media, online reviews, and digital platforms can improve consumers' perceptions of the clinic's service quality (Brand Image) while fostering a sense of security and trust in choosing the clinic (Brand Trust).